What determines stock market behavior in Russia and other emerging countries? - Iikka Korhonen; Anatoly Peresetsky (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
We empirically test the dependence of the Russian stock market on the world stock market and world oil prices in the period 1997:10-2012:02. We also consider three Eastern European stock markets (Poland, the Czech Republic, and Hungary), as well as two markets outside Europe (Turkey and South Africa). We apply a rolling regression to identify periods when oil prices or stock indices in the US and Japan were important. Surprisingly, oil prices are not significant for the Russian stock market after 2006. A TGARCH-BEKK model is employed to assess the degree of correlation between markets, taking into account the global market stochastic trend. We find that correlation between markets increased between 2000 and 2012. Growth was especially high in Eastern European markets during 2004-2006, which is likely connected with the EU accession of these countries in 2004.
URN:NBN:fi:bof-201408072224
Keywords: G10; G14; G15; C5; 330; Russian stock market; oil; financial market integration; stock market returns; news; emerging markets; transition economies